(untitled) (Journal Of Educational and Psychological Researches, 2023)
The research aims to identify the level of selective visual attention among students of the faculties of education at the University of Mosul. To achieve the goal of the research, the researchers chose a stratified random sample of students from the faculties of education at the University of Mosul for the academic year (2020-2021). The sample size was (652) students from the scientific and humanitarian specializations, the second and fourth stages. The researchers developed a test of multiple-choice to measure the selective visual attention, which consisted of (42) items. The results revealed that the students of the faculties of education for human sciences have an appropriate level of selective visual attention. There are statistically significant differences at the level of significance (0.05) in the selective visual attention among students of the faculties of education in favor of females. As for specialization, it was in favor of humanitarian specialization. There are no statistically significant differences between the students of the second and fourth stages. In the light of these results, the researchers came out with a number of conclusions, recommendations, and suggestions